Packaging and storage of fruits and vegetables : emerging trends - Alam, Tanweer (Postharvest biology and technology book series., 2021)
"This new volume shares a plethora of valuable information on the recent advances in packaging and storage technologies used for quality preservation of fresh fruits and vegetables. This book, with chapters from eminent researchers in the field, covers several essential aspects of packaging and storage methods and techniques generally used in fruit and vegetables. Important considerations on selection and characteristics of packaging materials, recent packaging methods, storage hygiene and sanitation issues along with recent trends in storage technology are discussed in this volume. Key features: Provides an inclusive overview of fruit and vegetable requirements and available packaging materials and storage systems, imparts an understanding of the fundamentals of the impact of packaging on the evolution of quality and safety of fruits and vegetables, covers fundamental aspects of packaging and storage requirements, including mathematical modeling and mechanical and engineering properties of packaging materials, provides an in-depth discussion of innovative packaging and storage technologies, such as MA/CA packaging, active packaging, intelligent packaging, eco-friendly materials, etc., applied to fruit and vegetables. Packaging and Storage of Fruits and Vegetables: Emerging Trends will be useful for graduate and postgraduate students and teaching professionals of horticultural science, food science and technology, packaging technology etc. It will also provide valuable scientific information to the academic scientific research community as well as to the packaging and storage industries for preservation of quality characteristics of fruits and vegetables. The professional community involved in handling processing and commercialization of horticultural crops will benefit as well."- Resumé vydavatel